Efficient Free Fatty Acid Reduction in Palm Oil Mill Effluent (POME) for Biodiesel Production: Challenges and Optimization Strategies - Indunil Chamara; Helitha Nilmalgoda; Eranga Wimalasiri (Challenges)
The increasing demand for fossil fuels has led the oil industry to explore biodiesel as a renewable alternative, which is crucial for advancing planetary health. Biodiesel offers environmental benefits and shares similar properties with petroleum diesel, making it a promising substitute. However, Palm Oil Mill Effluent (POME), containing sludge palm oil (SPO), presents challenges due to its high free fatty acid (FFA) content. This study proposes novel optimization strategies to reduce FFAs in SPO and improve biodiesel yield. A combination of base neutralization, esterification, and transesterification processes was employed. Neutralization with sodium hydroxide (NaOH) at concentrations ranging from 0.1% to 0.5% w/w was followed by esterification using sulfuric acid (H2SO4) with varying methanol-to-oil ratios. The optimal FFA reduction of 2.26% was achieved at a 6:1 methanol ratio. Transesterification with a 7:1 methanol-to-oil ratio yielded the highest biodiesel output of 71.25%. The biodiesel met ASTM standards, with a calorific value of 40.01 MJ/kg, a flash point of 180.5 °C, and a density of 0.86 g/cm3. Economic analysis estimates an annual net profit of USD 244,901,600, demonstrating that this approach provides a financially viable solution while advancing planetary health by reducing dependency on fossil fuels, mitigating climate change, and supporting sustainable fuel production.